2019
DOI: 10.1088/1755-1315/347/1/012079
|View full text |Cite
|
Sign up to set email alerts
|

Development of Partial Least Square (PLS) Prediction Model to Measure the Ripeness of Oil Palm Fresh Fruit Bunch (FFB) by Using NIR Spectroscopy

Abstract: In order to develop a model for predicting the oil palm Fresh Fruit Bunch (FFB) ripeness, a rapid and non-destructive method such as NIR spectroscopy is utilized. This method has shown its capability to determine the quality of some crops by predicting their internal chemical contents. The objective of the research is to investigate the feasibility of NIR spectroscopy to predict water and oil content in FFB by developing a calibration model. Sixty samples of FFB were scanned by using NIRFlex N-500 spectrometer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…NIR spectroscopy can be used to analyse the components in the citronella oil fraction. These results are in agreement with (Iqbal et al 2019;Windawati et al 2019;Novianty et al 2020), which confirm that the PLS method can improve the accuracy of the NIR spectroscopy analysis to predict the various chemical compounds in materials, such as the main components in oil. This study indicated that the model to predict the rhodinol content using the PLS method could be reliable in the initial stage of the spectral smart sensor development.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…NIR spectroscopy can be used to analyse the components in the citronella oil fraction. These results are in agreement with (Iqbal et al 2019;Windawati et al 2019;Novianty et al 2020), which confirm that the PLS method can improve the accuracy of the NIR spectroscopy analysis to predict the various chemical compounds in materials, such as the main components in oil. This study indicated that the model to predict the rhodinol content using the PLS method could be reliable in the initial stage of the spectral smart sensor development.…”
Section: Resultssupporting
confidence: 84%
“…This model is combined with chemometric techniques, which is a multivariate data analysis using the partial least square (PLS) regression method. PLS is a quantitative analysis method widely used in developing ideal qualities for linear analysis (Iqbal et al 2019). It also reduces the dimensions of the data The NIR transfectant spectrum data are used to develop the rhodinol levels prediction model with the GC-MS results of the chemical content information.…”
Section: Resultsmentioning
confidence: 99%
“…The x axis is associated with the wavelength ranges of the camera detector, lens, spectrograph, and halogen lamps of 400-1000 nm region. The visible-infrared spectrum has higher intensities in the region of 700-900 nm, the same fashion found in similar research of hyperspectral and infrared imaging on oil palm fresh fruit bunches [25], [27]. The measurement using four-band optical sensors showed higher reflectance intensities in the infrared region (700-900 nm) due to fewer absorbances by chlorophyll and anthocyanin in the mesocarp layer [22].…”
Section:  Issn: 1693-6930supporting
confidence: 81%
“…A detection system has used a 670 nm light source and an optical sensor to determine the FFB ripeness levels [22]. Moreover, imaging techniques such as thermal imaging [23], laser-induced fluorescence imaging [24], and near-infrared (NIR) spectroscopy [25] have been proposed to determine and predict FFB ripeness.…”
Section: Introductionmentioning
confidence: 99%
“…A familiar example of the technology is MRI scans which are most common in hospitals. (Iqbal, Herodian, and Widodo, 2019) captured NIR spectral data with the help of NIR camera for oil palm FFB ripeness detection.…”
Section: Nir Cameramentioning
confidence: 99%